Taḥlīl Muḥtawa al-Mufradāt fī Kitāb “al-Lughah al-ʿArabiyyah” li al-Ṣhaf al-Tāsiʿ al-Tsānawī wifqa Maʿāyīr Jaudat al-Muḥtawa al-Lughawī lil-Khoulī: Analysis of Vocabulary Content In The Arabic Language Book for The Ninth Grade Of Secondary School According to The Quality Standards of The Linguistic Content Of Al-Khouli - Jajang Komaludin; Ma’rifah Munjiah; Nuril Mufidah (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2024)
Vocabulary is a fundamental element in all languages, and there is no language without the evidence of vocabulary. However, the attention given to it in some educational materials has not met the required standards; instead, it needs to be reviewed, scrutinized, and addressed again. The study revealed the appropriateness of the vocabulary content in the